2009
DOI: 10.1002/prca.200800167
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of breast cancer tissue reveals upregulation of actin‐remodeling proteins and its relevance to cancer invasiveness

Abstract: There is an emerging interest in protein expression profiling with the aim of identifying novel diagnostic markers and therapeutic targets in breast cancer. We analyzed breast cancer tissues by 2-D DIGE using a narrow range IPG strip (pH 5.5-6.7) after the immunodepletion of serum albumin and Ig. Sixty-three protein spots were detected with more than 61.8-fold differences (p ,0.05 for three technical replicates) from a set of tissue samples in which three tumor and three nontumor samples were randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…The choice was based on the reports of these two proteins involved in key pathways of kidney or any other cancers in the literature as suggested in the Materials and Methods. Coronin 1A is an actin remodelling protein that has been reported to be overexpressed in breast cancer (Kim et al , 2009a; Klopfleisch et al , 2010). Our immunohistochemical results revealed that Coronin 1A is not expressed by the cells of the primary renal cancer (Figure 3A), but was highly expressed in the infiltrating lymphocytes in all the eight renal cancer specimens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice was based on the reports of these two proteins involved in key pathways of kidney or any other cancers in the literature as suggested in the Materials and Methods. Coronin 1A is an actin remodelling protein that has been reported to be overexpressed in breast cancer (Kim et al , 2009a; Klopfleisch et al , 2010). Our immunohistochemical results revealed that Coronin 1A is not expressed by the cells of the primary renal cancer (Figure 3A), but was highly expressed in the infiltrating lymphocytes in all the eight renal cancer specimens.…”
Section: Resultsmentioning
confidence: 99%
“…Coronin 1A could be a potential biomarker to assess the degree of TILs in the renal cancer, but this needs to be further studied. Coronin 1A was shown to be significantly correlated with development and migration of breast cancer cells (Kim et al , 2009a), compared with normal cell lines. Upregulation of Coronin 1A has been reported by others in RCC samples (Perroud et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, coronin 1A was found to be elevated in human breast cancer, and over-expression of coronin 1A in SK-BR3 breast cancer cells increased their invasion into Matrigel. 31 …”
Section: Discussionmentioning
confidence: 99%
“…WDR1 plays a crucial role in cytokinesis and cell migration and may be important in the ability of cancer cells to proliferate and invade surrounding tissues . Overexpression of WDR1 was reported in different cancers, including breast cancer, ovarian carcinoma, and thyroid neoplasia …”
Section: Discussionmentioning
confidence: 99%